Structural properties of Ge nano-crystals embedded in SiO2 films from X-ray diffraction and Raman spectroscopy - Rolo, Anabela G. (1998)
SiO2 films containing small particles of Ge were grown using the r.f.-magnetron sputtering technique. The films were studied by means of X-ray diffraction (XRD) and Raman spectroscopy. XRD studies revealed diamond structure of Ge particles in the films grown at temperatures higher than 500ºC. The dependence of the average size of Ge nanocrystals, determined by fitting the X-ray spectra (13-63 Aº), on the substrate temperature, r.f.-power and the fraction of semiconductor in the target was determined. For higher-temperature grown films containing crystalline Ge particles, a pronounced peak due to confined optical phonons was observed in Raman spectra, while for those grown at lower temperature, there is just a broad band seen below 300 cm-1. A theoretical model is applied to describe the contribution of optical phonons confined in small Ge spheres.